Dampak Faktor Manusia dan Pengoptimalisasian Terhadap Integritas Data Perusahaan Dalam Lingkungan Bisnis - Adhelia, Dhea Putri; Nasution, Muhammad Irwan Padli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Data integrity is a crucial element in the business environment, as it impacts the decision-making process and operational success. One of the main causes affecting data integrity is human factors, which include individual errors, behavior, and work ethic. The research aims to evaluate the impact of human factors on data integrity in a business context, as well as dig into strategies to mitigate risks that may arise. Using a qualitative approach, identify various ways in which human error and behavior can threaten data accuracy and reliability, as well as provide recommendations for increased awareness and training among staff processes